2006
DOI: 10.1506/2607-8pdh-wkcv-r3rd
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Test of the Interaction of the Insurance and Information‐Signaling Hypotheses in Auditing*

Abstract: Three incentives for hiring auditing services have been proposed in the literature: (1) to signal outsiders about the company's prospects, (2) to provide a potential source of loss recovery for investors (insurance), and (3) to reduce agency costs. The objective of this study is to examine the potential for the first two (signaling and insurance) to interact while controlling for agency costs. We conduct an experiment in which highly experienced financial analysts provide stock price estimates for a company th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…(e.g. Dye, 1993;O'Reilly et al, 2006), including studies that specifically focus on the Belgian context (e.g. Sarens et al, 2012), and on interviews with both auditors and managers to be able to make the translation from a general product/service to the specific service of auditing as accurately as possible (see Table 1 for an overview of all the items).…”
Section: Explanatory Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…(e.g. Dye, 1993;O'Reilly et al, 2006), including studies that specifically focus on the Belgian context (e.g. Sarens et al, 2012), and on interviews with both auditors and managers to be able to make the translation from a general product/service to the specific service of auditing as accurately as possible (see Table 1 for an overview of all the items).…”
Section: Explanatory Variablesmentioning
confidence: 99%
“…(e.g. Dye, 1993;O'Reilly et al, 2006) and on interviews with both auditors and managers to make this translation from the value perception towards a general product/service to the value perception towards the specific service of auditing as accurate as possible.…”
Section: Introductionmentioning
confidence: 99%
“…One of the reasons is an ongoing perception, especially among users and regulators, that there is still room for improving the form and content of the audit report. This perception is supported by academic research showing that although there is support that audit reports have information value for different groups of users such as investors (e.g., Chen and Church, 1996;Ghicas et al, 2008), loan officers (e.g., Guiral-Contreras et al, 2007;Schneider and Church, 2008) and financial and investment analysts (e.g., Dúrendez Gómez-Guillamón, 2003;O'Reilly et al, 2006), there is also evidence to the contrary (e.g., Wright and Robbie, 1996; Bartlett and Chandler, 1999;Pucheta Martínez et al, 2004), suggesting the presence of an information gap. 1 Furthermore, prior research provides ample evidence of an audit expectation gap, particularly in relation to auditor reporting, showing that there are significant perceptual differences between auditors and users as to the messages conveyed by the audit report (e.g., Innes et al, 1997;Gay et al, 1998;McEnroe and Martens, 2001).…”
Section: Introductionmentioning
confidence: 95%
“…Many of the prior studies have shown that auditing opinions provide a clear signal summarizing information on firms for use by outsider investors (Dye, 1993; Franz, Crawford and Johnson, 1998; Willenborg, 1999; O’Reilly, Leitch and Tuttle, 2006). Lennox (2000) found that highly leveraged companies, who clearly had inherently higher bankruptcy risk, were also more likely to receive modified audit reports, while Haskins and Williams (1990) and Citron and Taffler (1992) also noted that financial distress was an important indicator and a strong reason for auditors to issue modified opinions.…”
Section: Introductionmentioning
confidence: 99%